Nickel‐Catalyzed Cross‐Electrophile 1, 2‐Silyl‐Arylation of 1, 3‐Dienes with Chlorosilanes and Aryl Bromides. (14th December 2022) - Pan, Qiu‐Quan; Qi, Liangliang; Pang, Xiaobo; Shu, Xing‐Zhong
Abstract: Catalytic, three‐component, cross‐electrophile reactions have recently emerged as a promising tool for molecular diversification, but studies have focused mainly on the alkyl‐carbonations of alkenes. Herein, the scope of this method has been extended to conjugated dienes and silicon chemistry through silylative difunctionalization of 1, 3‐dienes with chlorosilanes and aryl bromides. The reaction proceeds under mild conditions to afford 1, 2‐linear‐silylated products, a selectivity that is different to those obtained from conventional methods via an intermediary of H(C)‐η 3 ‐π‐allylmetal species. Preliminary mechanistic studies reveal that chlorosilane reacts with 1, 3‐diene first and then couples with aryl bromide. Abstract : A nickel‐catalysed reductive silylarylation of 1, 3‐dienes using chlorosilanes and aryl bromides is reported. The reaction affords 1, 2‐linear‐silylated products, a selectivity that is distinct from those obtained with conventional hydro‐ and carbosilylation methods. This work shows the possibility to achieve the silyl‐functionalization of unsaturated bonds using readily available chlorosilanes.